2015
DOI: 10.1371/journal.pone.0129196
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Cell Death Induced by Resveratrol Is Partially Mediated by the Autophagy Pathway in Human Ovarian Cancer Cells

Abstract: Resveratrol (trans-3,4,5’ –trihydroxystilbene) is an active compound in food, such as red grapes, peanuts, and berries. Resveratrol exhibits an anticancer effect on various human cancer cells. However, the mechanism of resveratrol-induced anti-cancer effect at the molecular level remains to be elucidated. In this study, the mechanism underlying the anti-cancer effect of resveratrol in human ovarian cancer cells (OVCAR-3 and Caov-3) was investigated using various molecular biology techniques, such as flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 39 publications
6
58
0
3
Order By: Relevance
“…To study more closely, we have chosen two breast cancer cell lines-MCF-7 (ER-positive) and MDA-MB-231 triple negative (ER, PR, and HER2 negative) which represents most common type breast cancers in human. In line with previous reports, [26][27][28] we observed a similar growth inhibitory effect of RVT as it decreased the viability of both MCF-7 and MDA-MB-231 cells by 48 hr (Supplementary Information Figure S1). In correlation to the previous reports, 20,29 RVT exposure increased the endogenous level of BRCA1, p53, as well as p21 transcript and protein in a concentration and exposure timedependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…To study more closely, we have chosen two breast cancer cell lines-MCF-7 (ER-positive) and MDA-MB-231 triple negative (ER, PR, and HER2 negative) which represents most common type breast cancers in human. In line with previous reports, [26][27][28] we observed a similar growth inhibitory effect of RVT as it decreased the viability of both MCF-7 and MDA-MB-231 cells by 48 hr (Supplementary Information Figure S1). In correlation to the previous reports, 20,29 RVT exposure increased the endogenous level of BRCA1, p53, as well as p21 transcript and protein in a concentration and exposure timedependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, autophagy induced by NaB was repressed by NAC (Figure I). To explain this effect of ROS on autophagy, we search numerous literatures and find some studies have demonstrate that several anticancer agents including resveratrol or cucurbitacin trigger autophagy through ROS production. One of the underlying mechanisms is that ROS oxidize Atg4 leading to the promoted autophagosome formation .…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have indicated that it plays important podocyte-protective roles in multiple kidney diseases, including DN. Compelling evidence has shown that resveratrol is capable of inducing autophagy in different cancer cell lines202122; however, nothing is known about its effect on autophagy induction in renal cells. In this study, we demonstrated that resveratrol effectively attenuates HG-induced apoptosis of podocytes via the activation of autophagy in db/db mice.…”
Section: Discussionmentioning
confidence: 99%